synthesis morpholine diamide by curing some aromatic - Baghdad Science Journal (مجلة بغداد للعلوم)
in this work many amide polymers were prepared according to the modification reaction of polyacryloyl chloride or poluacrulic acid with different primary amines to mesuringninizing hormone were investgaited prior tq surgery in 10 postmenopaisal women with benign and 10 postmenopausal women with maliganant healthy